2017
DOI: 10.1117/12.2254060
|View full text |Cite
|
Sign up to set email alerts
|

Needle tip visibility in 3D ultrasound images

Abstract: Aim Needle visibility is crucial for effective and safe ultrasound-guided interventional procedures. Several studies have investigated needle visibility in 2D ultrasound imaging, but less information is available for 3D ultrasound imaging, a modality that has great potential for image guidance interventions. We performed a prospective study, to quantitatively compare the echogenicity of various commercially available needles in 3D ultrasound images used in clinical practice under freehand needle introduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A visible surface must produce echoes differently from its surroundings; that is, the FG and BG areas must be segregable. The contrast-to-noise ratio (CNR) (Arif et al 2018) aptly quantifies surface visibility as it evaluates the difference in signal strengths. In turn, echogenicity resembles a surface property, independent of BG conditions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A visible surface must produce echoes differently from its surroundings; that is, the FG and BG areas must be segregable. The contrast-to-noise ratio (CNR) (Arif et al 2018) aptly quantifies surface visibility as it evaluates the difference in signal strengths. In turn, echogenicity resembles a surface property, independent of BG conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Instead of reintroducing the needle in numerous relevant orientations, a rotational platform was used to study a full range of insertion angles. Needle visibility was analyzed in polyvinyl alcohol (PVA), which has good tissue resemblance in US images (Arif et al 2018;Surry et al 2004). Needle echogenicity was analyzed in water to reduce attenuations and distortions.…”
Section: Aim and Approachmentioning
confidence: 99%
“…Needle visibility is strongly dependent on the insertion angle, where the highest values are seen at orthogonal needle‐probe angles (Figures 4 and 5). Other studies also reported an increase in visibility of the needle near the 90° angle 13,32 . This effect is caused by specular reflections of US waves at the needle surface, returning to the probe for orthogonal angles, but not for acute angles.…”
Section: Discussionmentioning
confidence: 84%
“…Arif et al. also obtained better visibility results for the ablation needles, including RFA, in a comparative study with commercial percutaneous needles 13 . However, they analyzed the visibility of the needle tips under 3D ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, current limitations still exist for visualizing and verifying needle applicator positions in 3D US liver images as the visibility can change with needle applicator insertion angle, depth, and size, in addition to the choice of transducer (i.e., curvilinear) and local anatomical acoustic reflections that result in complicated images containing shadows and reverberation artifacts with unclear line-like interfaces. 16,17 Attempts have been made using a variety of needle applicator-enhancing techniques to address these localization concerns for the physician by incorporating additional features like echogenic coatings, 18 magnetic or optical tracking systems, 19 robotic needle steering, 20 augmented reality, 21 and US beam steering. 22 Although many options seem promising, all of the above choices add increased cost and complexity relative to the conventional procedure, which can be a limiting factor for widespread dissemination.…”
Section: Introductionmentioning
confidence: 99%